The Health Economic Impact of Nephrotic Syndrome in the United States. Issue 6 (30th June 2022) - Simon, Christine A.; Salmon, Eloise; Desmond, Hailey E.; Massengill, Susan F.; Gipson, Wilson P.; Gipson, Debbie S.
Key Points: Median annual direct costs (including medication, diet, emergency room visits, hospitalizations, and clinic visits) were $3464 (interquartile range [IQR] $844–$5865) for adult patients and $1687 (IQR $1035–$4763) for caregivers. The time spent planning/prepping meals was 183 h/yr (IQR 114–331) for adults and 173 h/yr (IQR 84–205) for caregivers. Providers can better understand the burden of living with nephrotic syndrome, consider barriers when treating patients, and develop supportive strategies. Visual Abstract: Abstract : Background: Nephrotic syndrome (NS) is a rare kidney syndrome with high morbidity. Although a common contributor to the burden of chronic kidney disease, the direct and indirect costs of NS to patients and family caregivers are unrecognized. The objective was to characterize the direct and indirect costs of NS to patients. Methods: Adults with NS and family caregivers of children with NS were eligible to participate if they had a diagnosis of primary NS, had disease for at least 1 year, and had no other severe health conditions. Data-collection surveys were generated with input from the Kidney Research Network Patient Advisory Board, and surveys were mailed to the eligible participants. Participants were provided $50 for the return of completed surveys. Costs were defined as either direct out-of-pocket costs or indirect costs ( e.g., time). Descriptive statistics, including percentage and median (interquartile range [IQR]) are reported. Results: Respondents included 28 adult patients and 17 caregivers of patients who were minors. Reported health insurance coverage included 35 (78%) with private insurance, 12 (27%) with public insurance, six (13%) with Children's Special Health Care Services, and one (2%) uninsured. Median annual direct costs were $3464 ($844–$5865) for adult patients and $1687 (IQR $1035–$4763) for caregivers. Of these costs, diet-associated costs contributed $1140 (IQR $600–$2400). The most substantial indirect cost was from the time spent planning/prepping meals (adults: 183 h/yr [IQR 114–331]; caregivers: 173 h/yr [IQR 84–205]). Conclusions: Adults and caregivers of children with NS face substantial disease-related direct and indirect costs beyond those covered by insurance. Following replication, the study will help health care providers, systems, and payers gain a better understanding of the financial and time burden incurred by those living with NS, consider barriers when treating patients, and develop supportive strategies.